2020
DOI: 10.1007/s00194-020-00382-4
|View full text |Cite|
|
Sign up to set email alerts
|

Häusliche Gewalt gegen Männer – auch ein rechtsmedizinisches Problem?

Abstract: Zusammenfassung Hintergrund Auch männliche Geschädigte von häuslicher Gewalt wenden sich mit ihren Verletzungen häufig zunächst an ihre Hausärzte/Hausärztinnen oder Ärzte/Ärztinnen in Notaufnahmen. Daher ist das weiterhin eher schambesetzte Thema „häusliche Gewalt gegen Männer“ für alle medizinischen Professionen relevant. Methode Es wurde eine retrospektive Datenanalyse für einen Fünfjahreszeitraum durchgeführt. Dabei wurde analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Reports on medicolegal characteristics of male victims of IPV in Germany are scarce. A recent German study reported on IPV injury patterns of 16 men examined over a 6-year period [15,16], while a portion of 11-12.8% of males among clinical-forensic examinations of IPV victims was observed in other European countries [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports on medicolegal characteristics of male victims of IPV in Germany are scarce. A recent German study reported on IPV injury patterns of 16 men examined over a 6-year period [15,16], while a portion of 11-12.8% of males among clinical-forensic examinations of IPV victims was observed in other European countries [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Besides public campaigns, training of healthcare professionals, law enforcement agencies and educators are important for both prevention and diagnosis of IPV. However, most IPV victim support centres in Germany offer services to female victims exclusively, therefore specific offers for affected males would be highly eligible [16].…”
Section: Introductionmentioning
confidence: 99%